PERLINDUNGAN HUKUM KONSUMEN TERHADAP PRODUK PANGAN KADALUWARSA - Nugroho, Ali; Ratnawati, Elfrida (Universitas Ekasakti, 2023)
The rampant distribution of expired food and drinks does not only occur before major holidays, but also occurs on weekdays, which is common in the community. Everyone, at one time either in a single position/alone or in a group with other people. under any circumstances, a citizen must be a consumer for a particular product or service, entitled to legal protection that must be provided by the state. One of the protections that must be provided by the state is consumer protection. This study uses a juridical method by conducting legal research that prioritizes literary materials which basically aims to find secondary data consisting of primary, secondary and tertiary legal materials. This is done so that people do not consume products or services that endanger safety, health, and so on, so that people get satisfaction. In RI Law. No. 8 of 1999, concerning consumer protection (UUPK). Legal protection for consumers can be in the form of non-litigation mechanisms, namely settlements without a judicial process based on Article 47 of Law No. 8 of 1999 concerning consumer protection. As well as the legal form of protection for consumers who experience losses from the distribution and trade of expired food is protection. laws to be upheld and enforced. The responsibility of the business actors for the losses they experience, the consumer can report it to the relevant parties or agencies.